Analysis of landslide kinematics integrating weather and geotechnical monitoring data at Tan Son slow moving landslide in Ha Giang province - Dao Minh, Duc; Vu Cao, Minh; Hoang Hai, Yen; Nguyen The, Loc; Do Minh, Duc (Vietnam Journal of Earth Sciences, 2023)
Rainfall infiltration on the slope increases pore-water pressure in the soil/ rock mass and may cause landslides. Therefore, the precipitation, pore-water pressure and displacement show the kinematic variation of a landslide. In recent years, several approaches have been proposed to investigate the kinematic behavior. Among them, the combination of time series data and geotechnical model has demonstrated its effectiveness in stage classification of landslide kinematics. This paper aims to analyze and classify the stages of landslide kinematic variation with integrating weather and geotechnical monitoring data of Tan Son market landslides. The real-time monitoring station for Tan Son slow-moving landslides were equipped with fixed-in-place inclinometer probes and standard pore-water pressure sensors. The results show that landslide kinematics consist of three stages: stabilization, accumulation, and displacement. The displacement of the landslides was heterogeneous process. The velocity of the landslides significantly increased when the pore-water pressure ratio (ru) at the sliding surfaces > 0.53. While it is almost impossible to notice any displacement when the ratio ru < 0.45. During the displacement state, the trend of inverse velocity variation gradually decreases to near zero hour/mm. In addition, early warnings of landslide can be released based on the kinematic stages and changes in inverse velocity in this study.